PARTICIPATING IN ECOTURISM ACTIVITIES IN BUSINESS GROUPS SOCIAL (KUPS) HARAU DISTRICT - Anggraeni, Sovia; Milantara, Noril; Lensari, S.Hut, M.Si, Delfy; Helida, Asvic (Universitas Muhammadiyah Palembang, 2024)
A forest is a unified ecosystem in the form of an expanse of land containing biological natural resources dominated by trees in a natural environment, one of which cannot be separated from the other (UU No. 41 of 1999). Forest Management Unit (KPH) is a forest management area according to its main function and designation, which can be managed efficiently and sustainably. Ecotourism or ecotourism (in English: ecotourism) is a tourism activity that is environmentally friendly by prioritizing aspects of nature conservation, aspects of socio-cultural economic empowerment of local communities, as well as aspects of learning and education. The aim of this research is to find out ecotourism in KUPS Harau District. Data collection in practice is carried out through direct observation techniques in the field and conducting interviews with supervisors in the field regarding the required data parameters. There are 4 KUPS in Harau District, namely, KUPS Kapalo Banda Taram, KUPS Guguak Keramat, KUPS Bukik Kumayan Lestari and KUPS HKm Maju Basamo. With different tourist attractions for each KUPS.